Transfer and transition practices in 96 European adult congenital heart disease centres. (1st April 2021) - Thomet, Corina; Schwerzmann, Markus; Budts, Werner; De Backer, Julie; Chessa, Massimo; Diller, Gerhard; Eicken, Andreas; Gabriel, Harald; Gallego, Pastora; Giamberti, Alessandro; Roos-Hesselink, Jolien; Swan, Lorna; et al.
Abstract: Background: Irrespective of initial treatment for congenital heart disease (CHD) in childhood, CHD is a lifelong condition, leaving patients at risk for complications. To support uninterrupted, age- and development-based care for young persons with CHD, guidelines and consensus papers emphasise the need for formal transition programmes, including transfer to adult CHD (ACHD) clinics. Here, we surveyed existing transfer and transition programmes in European ACHD centres. Our aims were to provide a contemporary view of transitional care for patients with CHD and to evaluate progress over the last decade. Methods: We conducted a descriptive, cross-sectional survey in 96 ACHD centres in Europe. A specific survey form was developed that sampled the practices of transfer and/or transition. We used a transfer-transition index to quantify adherence to quality indicators of successful transfer and transition. Results: Of the 96 ACHD centres, 40 (41.7%) offered a formal transition, and 85 (88.5%) had structured transfer from paediatric to ACHD care. Although 31% of the centres performed at a 'good' level on the transfer-transition index, only 4 (4.2%) satisfied all criteria. Most centres with a transition programme offered education and support through a dedicated transition specialist, who was a master's-prepared nurse in most centres. A minority of the ACHD centres offered a flexible transition process, starting at least two years before transfer. Conclusions: Nearly half of the included ACHD centres offered a formal transition programme, and almost 90% offered structured transfer. Despite some improvements since 2009, most of the programmes lacked an age- and development-based approach. Highlights: The majority of CHD centres in Europe offer a structured transfer from paediatric to adult care. Although the number of centres with formal transition increased over time, time, only a minority follows the recommendations to the fullest maximum. All transition programmes included a dedicated transition specialist; the role is often taken up by nurses.